THE CONTRIBUTION OF FISHERIES SUBSECTOR TOWARD GROSS REGIONAL DOMESTIC PRODUCT OF BATAM CITY RIAU ISLAND PROVINCE - Tri Putra; Lamun Bathara; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on January 2016 in Batam City Riau Island Province. The location of the specified research by (purposive). The methods used in this research is survey method, data used in this research is the data set of the time of year 2009 until 2013. The aim of this study: 1) To analyze the fisheries subsector contribution toward Gross Regional Domestic Product (GDP) and employment in Batam city in 2009-2013, 2) To analyze the base or non base fisheries subsector in the development of fisheries in Batam based on Gross Regional Domestic Product and employment in the years 2009-2013, 3) knowing the linkages between the fisheries subsector with other sectors in Batam based on the Gross Regional Domestic Product an based on employment in the years 2009-2013. Based on the research, the contribution of the fisheries subsector Batam toward Gross Regional Domestic Product in 2009-2013 are 0,51%, 0,50%, 0,50%, 0,47%, and 0,45%. While the contribution of the fisheries subsector in Batam city based on indicators of labor from 2009-2013 are 0,41%, 0,40%, 0,34%, 0,38% and 0,37%. Fisheries subsector is a non base subsector based on indicators of Gross Regional Domestic Product, but based on the indicators of labor is a base subsector. Fisheries subsector provides the Multiplier Effect  value between 150.57 to 4416.43 based on indicators of Gross Regional Domestic Product, while based on the indicators of labors values ​​range between -1 220 until 445 people.   Keywords : Contributions, GDP, Multiplier Effect